The mediating role of innovation in the relationship between market orientation and university performance in Pakistan - Khuwaja, Faiz Muhammad (2017)
Universities globally are going through a paradigm shift with a need to become more innovatively market-oriented to handle the issue of growing competition for funding, as well as attracting/retaining the international/local competent students and academicians. However, there appears to be a dearth of research on how such state of affairs could be addressed, particularly in the emerging economies like Pakistan. In the light of resource-based theory (RBT), as well as organizational-learning theory (OLT), literature suggests that market-orientation (MO) and innovation are to be the desirable unique resources, as well as the guiding philosophies, to enable universities for a more competitive performance. Hence, this study investigated how resources like marketorientation (MO), and innovation, can influence university performance (UP). The study also tested empirically the potential mediating effect of innovation on the MOUP relationship. In addition, how the dimensions of MO influenced the innovation and university performance (UP) were also tested empirically in the universities of Pakistan. Results of the PLS path modelling (with 369 respondents from the target public-sector universities) firstly confirmed significant effect of the “universal construct of MO” and two of its dimensions “the advising and mentoring, as well as the intelligencegeneration and response” on UP. However, one dimension of MO, which is the administration-leadership, was not significantly supported to directly influence the UP. Secondly, the study confirmed that there were significant direct effects of the “universal construct of MO”, as well as all of its dimensions, on innovation. Thirdly, the study also found that there was a significant effect of innovation on UP. Furthermore, the bootstrapping results found significant mediation of innovation between the MO-UP relationship. Hence, the results show that UP can be directly enhanced through MO and innovation. Even the use of innovation as a mediator can further strengthen the MO-UP relationship. Based on the findings, the study offers theoretical and practical implications, followed by its limitations and directions, for future research.